Polysaccharide Chain Length of Lipopolysaccharides From Salmonella Minnesota Is a Determinant of Aggregate Stability, Plasma Residence Time and Proinflammatory Propensity in vivo - Sali, Wahib; Patoli, Danish; Pais de Barros, Jean-Paul; Labbé, Jérôme; Deckert, Valérie; Duhéron, Vincent; Le Guern, Naig; Blache, Denis; Chaumont, Denis; Lesniewska, Eric; Gasquet, Benoit; Paul, Catherine; et al. (Frontiers in Microbiology, 2019)
Lipopolysaccharides (LPS) originate from the outer membrane of Gram-negative bacteria and trigger an inflammatory response via the innate immune system. LPS consist of a lipid A moiety directly responsible for the stimulation of the pro-inflammatory cascade, and a polysaccharide chain of variable length. LPS form aggregates of variable size and structure in aqueous media, and the aggregation/disaggregation propensity of LPS is known as a key determinant of their biological activity. The aim of the present study was to determine to which extent the length of the polysaccharide chain can affect the nature of LPS structures, their pharmacokinetics and eventually their proinflammatory properties in vivo. LPS variants of Salmonella minnesota with identical lipid A but with different polysaccharide moieties were used. The physical properties of LPS aggregates were analysed by zetametry, dynamic light scattering and microscopy. The stability of LPS aggregates was tested in the presence of plasma, whole blood and cultured cell lines. LPS pharmacokinetics were performed in wild-type mice. The accumulation in plasma of rough LPS (R-LPS) with a short polysaccharidic chain was lower and its hepatic uptake was faster as compared to smooth LPS (S-LPS) with a long polysaccharidic chain. The inflammatory response was weaker with R-LPS than with S-LPS. As compared to S-LPS, R-LPS formed larger aggregates, with a higher hydrophobicity index, a more negative zeta potential and a higher critical aggregation concentration. The lower stability of R-LPS aggregates could be illustrated in vitro by a higher extent of association of LPS to plasma lipoproteins, faster binding to blood cells and increased uptake by macrophages and hepatocytes, compared to S-LPS. Our data indicate that a long polysaccharide chain is associated with the formation of more stable aggregates with extended residence time in plasma and higher inflammatory potential. These results show that polysaccharide chain length, and overall aggregability of LPS might be helpful to predict the proinflammatory effect that can be expected in experimental settings using LPS preparations. In addition, better knowledge and control of LPS aggregation and disaggregation might lead to new strategies to enhance LPS detoxification in septic patients.